PENGARUH SUBTITUSI TEPUNG Azolla microphylla DAN LIMBAH TEPUNG SISA PENGGORENGAN TERHADAP KECERNAAN BAHAN KERING DAN BAHAN ORGANIK ITIK PEDAGING - Alwi Sihab; Nita Opi Ari kustanti; Alfan Setya Winurdana (Universitas Islam Balitar, 2023)
The objective of this research was know to the effect and optimize level of azolla microphylla used in ration on dry and organic matter digestibility for meat duck. This research use 100 meat duck aged 4 days, randomly divided into 5 treatment combinations Completely Randomized Design (CRD) wich divided into five treatment and treatment each (P0, P1, P2, P3,P4) consist of four replication. Each replication used 5 meat ducks. The result of this research in each treatment (P0,P1,P2,P3,P4) on the largest dry matter intake at P0 3523,38, lowest at P4 2998,36 g/head/period. The largest organic matter intake at P0 3257,65, the lowest at P4 2704,14 g/head/period. The largest dry matter digestibility in P2 81,66%, lowest at 79,19% and the largest organic matter digestibility at P3 95,23%, lowest at P0 93,15%. The conclusion in addition of Azolla microphylla affected dry matter consumption, organic matter consumption, and dry matter digestibility, but had no effect on organic matter digestibility.